The study of customer Perception and expectation toward food presentation / Noorliza Zainol, Hashim Fadzil Ariffin and Abdul Rahman Ahmad Rozali - Zainol, Noorliza; Ariffin, Hashim Fadzil; Ahmad Rozali, Abdul Rahman (Universiti Teknologi MARA, Cawangan Melaka, 2018)
Every sole ingredient used in plating foods may influence foods presentation. Other elements in food presentation such the foods’ color, temperature, variety, freshness, shape and the materials of the tableware used; need to be balance on plate to increase the level of palatability. These elements in a food’s plate may act as the communication and marketing tool to the customers. The study was done through a survey participated by 300 students of University Technology Mara (Penang). The purpose of this study is to examine the elements that manipulate customers’ expectation on food presentation and to investigate the degree of customer perception toward food presentation. In this study, the researcher found that the food presentation has significantly impacted on the way in which customers consume their foods, the different color, shape, size and variety of food, the used of tableware and arrangements of foods must work together pleasantly in order to stimulate customer appetite. It may beneficial to all the food developers as the art may significantly changes by manipulating the factors and resulting in influencing the customers’ foods’ choices.